Effects of Inference Demands and Structural Complexity on Transitive Inference Processing: Comment on Lee and Kwon (2013). Issue 3 (December 2014) - Kwon, Nayoung
In a recent study that investigated the processing of transitive inferences, Lee and Kwon (2013) concluded that only informational complexity leads to processing difficulty, that structural complexity affects earlier stages of processing than informational complexity, and that working memory resources are shared between sentence processing and other cognitive processes. Here, the evidence for these findings is scrutinized, and it is argued that there exist significant difficulties in drawing such conclusions based on the methodology and presented data.